Effect of methylglyoxal on Parkinson’s disease pathophysiology in the rotenone model - YILMAZ, BETÜL; GÜLHAN, REZZAN (My University, 2024)
Objective: Type 2 diabetes mellitus patients have been reported to have a higher incidence of Parkinson’s disease. This study aimed to explore the effect of advanced glycation end products precursor methylglyoxal (MGO) on the pathophysiology of Parkinson’s disease in a rotenone model. Materials and Methods: Adult female Wistar rats (n=42) were divided into four groups. Rotenone toxicity was assessed by daily weight measurements and mortality rates. Effect of MGO on blood glucose was evaluated. Locomotor activity, rearing, and rotarod tests were performed to evaluate motor functions, and for neurodegeneration, tyrosine hydroxylase immunoreactivity in the striatum and substantia nigra regions was assessed. Results: The mortality rate was 9% in the rotenone-applied rats. The mean weight, locomotor activity, rearing activity, and longest time spent on a rotarod were lower in the MGO+Rotenone group than in the Control group. Tyrosine hydroxylase immunoreactivity in the striatum rostral to the anterior commissure in the MGO+Rotenone group was lower than that in the Control and MGO groups. The number of tyrosine hydroxylase positive cells in the substantia nigra pars compacta was comparable among the groups. Conclusion: When nigrostriatal degeneration was triggered, MGO was found to worsen motor dysfunction and increase damage to dopaminergic neuron projections.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Locomotor activity; Methylglyoxal; Parkinson’s disease; Rotenone; Type 2 diabetes mellitus; Tyrosine hydroxylase